Analytical evaluation of intra domain mobility approach in NEMO environment - Shayla, Islam; Hassan Abdalla Hashim, Aisha; Habaebi, Mohamed Hadi; Hassan, Wan Haslina; Abdul Latif, Suhaimi; Mohd. Ramli, Huda Adibah; Hasan, Mohammad Kamrul (Maxwell Scientific Publications, 2014)
Network Mobility Basic Support Protocol (NEMO BSP) is considered as the most widespread network mobility protocol at the present time which is a logical extension of the MIPv6 operation. Hence, Location Update (LU) procedure of NEMO BSP is almost similar to MIPv6 registration apart from setting of the MR flag and sending of prefix in the Binding Update (BU). However, in NEMO network, providing an uninterrupted Internet connectivity during handoff (seamless handoff) is still an open issue for the current researchers in terms of handoff delay, packet loss, service disruption time and signaling overhead respectively. To concentrate on these issues, in this study, an Intra Domain Mobility scheme in NEMO (IDM-NEMO) is proposed that aims to reduce signaling overhead by incorporating an improved version of Fast HMIPv6 scheme with NEMO network to attain continuous Internet connectivity at the time of movement from one subnet to another. Additionally, in order to analyze the location update cost, a mathematical model has been developed and compared with the standard NEMO BSP. The analytical result demonstrates that the proposed scheme reduced location update cost by 52% than that of NEMO-BSP.